Efek Pemberian Asam Amino untuk Mencegah Acute Kidney Injury (AKI) Pasca-Operasi Jantung : Tinjauan Sistematik - Rahman, Lukman Nur; Makarim, Munzir; Anjar, Muh. Azrief Khaidir; Maulana, Muh. Syawaludin Sakti; Trisiyambudin, Rais; Sampe, Greyson Efraldi; Faali, Rifal; Falah, Muhammad Hilmi; Furqon, Muh. Ikmaluddin; Rizal, Dzar Ghifari Muh (Cermin Dunia Kedokteran, 2025)
Introduction: The administration of amino acids can be a safe and effective approach to reducing the risk of acute kidney injury (AKI) following cardiac surgery. Methods: In this systematic review, data were obtained from scientific databases PubMed, ProQuest, ScienceDirect, and Google Scholar, covering publications from January 1 to November 1, 2024. This systematic review analyzed 3 randomized controlled trials involving a total of 3,647 patients. Results: AKI was observed in 26.6% patients in the amino acid group compared to 31.9% in the control group (RR = 0.67; 95% CI [0.43–1.06]; I² = 52.5%; p = 0.0854). Additionally, the risk of stage 1 AKI (21.1% vs 24.5%; RR 0.86; 95% CI [0.77–0.96]; I² = 0%) and stage 3 AKI (0.15% vs 0.3%; RR 0.52; 95% CI [0.34–0.81]; I² = 0%) was significantly lower in the amino acid group. No serious adverse events were reported in the included studies. Risk of bias was assessed using the Cochrane Risk of Bias-2 (RoB2) tool, and data analysis was performed using R software. Conclusion: Findings suggest that amino acids offer clinical benefits in AKI prevention, particularly in stages 1 and 3, without increasing the risk of severe adverse effects